A Chitosan Derivative Containing Both Carboxylic Acid and Quaternary Ammonium Moieties for the Synthesis of Cyclic Carbonates. Issue 16 (21st July 2016) - Besse, Vincent; Illy, Nicolas; David, Ghislain; Caillol, Sylvain; Boutevin, Bernard
Abstract: Chitosan, a renewable feedstock, is modified and used as a catalytic support in the presence of potassium iodide. The system is highly efficient towards the incorporation of carbon dioxide (CO2 ) into epoxides. It demonstrates very good thermal stability and is recyclable more than five times without loss of activity. The optimal reaction conditions were determined using allylglycidyl ether as a model and extended to a wide range of other epoxides. Cyclic carbonates were obtained with very high yield in a few hours under mild conditions (2–7 bar≈0.2–0.7 MPa, 80 °C) and no solvent. Abstract : Renewable catalysis : A chitosan‐based catalyst for epoxide carbonation is described. The catalyst is efficient for the synthesis of a wide range of compounds under significantly milder operating conditions (pressure and temperature) compared to previously reported bio‐based supported catalysts. It is also recyclable more than five times without loss of activity.